2019
DOI: 10.1016/j.addbeh.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the role of delay discounting and craving in gambling chasing behavior

Abstract: Chasing is a central feature of gambling disorder and refers to the attempt by individuals to recover financial losses by continuing to gamble. Although several efforts have been made to individuate the factors involved in the complex phenomenon of chasing, little is known regarding its association with delay discounting and craving, both considered important in the development and maintenance of gambling disorder. In the present study, the interplay between chasing, delay discounting, and craving (while contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 66 publications
5
27
1
Order By: Relevance
“…As expected and consistent with previous research on both adults and adolescents (e. g. Cosenza et al, 2019a , Hing et al, 2016 , Nigro et al, 2017 , Raylu et al, 2016 , Welte et al, 2015 ; for reviews, see Delfabbro, Thomas, & Armstrong, 2018), boys reported significantly higher levels of gambling severity, alcohol consumption, and craving. In line with prior findings, chasing behavior did not vary by gender ( Bibby, 2016 , Campbell-Meiklejohn et al, 2008 , Lister et al, 2016 , O'Connor and Dickerson, 2003 , Worhunsky et al, 2017 ) or as a function of the experimental condition ( Ciccarelli et al, 2019a , Ciccarelli et al, 2019b , Lister et al, 2016 , Nigro et al, 2018a ). Rather, the results of logistic regression analysis suggested that the choice to stop or continue playing depend on both a strong, urgent desire to gamble and the anticipation of immediate positive subjective experiences from gambling, whereas chasing proneness was predicted not only by anticipation and desire to gamble, but also by alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…As expected and consistent with previous research on both adults and adolescents (e. g. Cosenza et al, 2019a , Hing et al, 2016 , Nigro et al, 2017 , Raylu et al, 2016 , Welte et al, 2015 ; for reviews, see Delfabbro, Thomas, & Armstrong, 2018), boys reported significantly higher levels of gambling severity, alcohol consumption, and craving. In line with prior findings, chasing behavior did not vary by gender ( Bibby, 2016 , Campbell-Meiklejohn et al, 2008 , Lister et al, 2016 , O'Connor and Dickerson, 2003 , Worhunsky et al, 2017 ) or as a function of the experimental condition ( Ciccarelli et al, 2019a , Ciccarelli et al, 2019b , Lister et al, 2016 , Nigro et al, 2018a ). Rather, the results of logistic regression analysis suggested that the choice to stop or continue playing depend on both a strong, urgent desire to gamble and the anticipation of immediate positive subjective experiences from gambling, whereas chasing proneness was predicted not only by anticipation and desire to gamble, but also by alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
“…”) and that self-rating of chasing might differ from chasing assessed by means of a behavioral task. However, the results of the present study dovetail with previous finding showing that the decision to persist in gambling may apart from gambling outcomes and may represent a personality trait-like characteristic contributing to gambling severity ( Ciccarelli et al, 2019a , Ciccarelli et al, 2019b , Nigro et al, 2018a , Nigro et al, 2018b ). This finding strongly supports the idea that nonchasers and chaser belong to quite different subtypes of gamblers as first postulated by Blaszczynski and Nower’s (2002) pathway models and is in accordance with Linnet et al (2006) , who hypothesized that chasing proneness “in addition to the addiction, may constitute a distinct entity or level of severity within pathological gambling” (p. 43).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations